Three-dimensional power Doppler ultrasound with a three-dimensional multislice view. Issue 3 (August 2015) - El-Mekkawi, Sherif F.; Bahaa, Ahmed M.; Akl, Sherif A.; Sorour, Rabab M.
<x xml:space="preserve">Abstract</x> Objective To evaluate the efficacy of three-dimensional power Doppler (3DPD) and 3D multislice view in distinguishing between benign and malignant endometrial lesions in women with postmenopausal bleeding (PMB) and endometrial thickness of 5 mm or more. Study design This was a diagnostic accuracy study. Patients and methods Women with PMB and an endometrial thickness of 5 mm or more on two-dimensional transvaginal sonography were evaluated by 3DPD before endometrial sampling to make a definitive histological diagnosis of endometrial lesions. Endometrial volume (EV), vascularization index (VI), flow index (FI), and vascularization–flow index (VFI) were calculated using Virtual Organ Computer-aided AnaLysis (VOCAL) software. 3D multislice view was used to increase the diagnostic accuracy of the above parameters (EV, VI, FI, and VFI) in the diagnosis of different endometrial lesions. The women included were divided into two groups: group 1 included 28 patients who had a histological diagnosis of endometrial carcinoma and group 2 included 32 patients who had a histological diagnosis of benign endometrial disorders. Results Sixty women with PMB were finally analyzed; 32 (53.3%) women had benign endometrial lesions and 28 (46.7%) had endometrial malignancy. Women in group 1 tended to have significantly thicker endometrium (11.11±3.61 vs. 5.78±0.94 mm; P=0.0001), larger EV (4.89±3.53 vs. 2.22±1.60; P=0.001), and higher 3DPD flow indices (P=0.0001) than those with benign endometrial lesions. There was a statistically significant difference between 3DPD and 3D multislice view, with increased vasculature in different planes in malignant cases than in benign cases (P=0.0001). The best logistic regression models for predicting malignancy [i.e. the models with the largest area under the curve (AUC)] included endometrial thickness and VFI (AUC 0.984 and 0.884). Conclusion Even though histopathological examination of the endometrium is the gold standard for the final diagnosis or exclusion of endometrial malignancy, EV, 3DPD indices, and 3D multislice view are good diagnostic tools in predicting endometrial malignancy in women with PMB.